2002
DOI: 10.1016/s0924-9338(02)80813-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking modulates neuroendocrine responses to ipsapirone in patients with panic disorder

Abstract: In 12 patients a moderate to marked improvement in all domains was observed upon treatment with 20-40 mg citalopram daily. Treatment for one year in the effective dose prevented recurrence of depressive symptomatology. P46.07 A rare case of neuroleptic malignant syndrome and the NMS spectrum concept It is concluded that citalopram is a well tolerated, safe, interaction-free and effective antidepressant in mentally retarded subjects with a depressive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We believe that adoption of this point of view will afford a better understanding of the pathophysiology of PTSD as well as the high comorbidity between smoking dependence and PTSD. In addition, application of techniques for characterizing the smoking patterns of research participants should be extended to studies of the neurobiological basis for other anxiety disorders (Breslau and Klein, 1999;Johnson et al, 2000;Broocks et al, 2002;Isensee et al, 2003;Schumann et al, 2004;McCabe et al, 2004). We hope that investigation of the relationship between nicotine dependence and PTSD or other anxiety disorders will lead to new methods of prevention and treatment of these severely debilitating and costly neuropsychiatric conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that adoption of this point of view will afford a better understanding of the pathophysiology of PTSD as well as the high comorbidity between smoking dependence and PTSD. In addition, application of techniques for characterizing the smoking patterns of research participants should be extended to studies of the neurobiological basis for other anxiety disorders (Breslau and Klein, 1999;Johnson et al, 2000;Broocks et al, 2002;Isensee et al, 2003;Schumann et al, 2004;McCabe et al, 2004). We hope that investigation of the relationship between nicotine dependence and PTSD or other anxiety disorders will lead to new methods of prevention and treatment of these severely debilitating and costly neuropsychiatric conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence suggest that serotonergic neurotransmission, including the regulation of 5-HT1A receptors, is affected by nicotine [39]. Recent studies showed that some of nicotine's psychotropic and endocrine effects are exerted by stimulation of 5-HT1A receptors on dorsal raphe neurons [40]. Increased cortisol secretion may play a role by inducing tryptophan 2,3-dioxygenase (tryptophan pyrrolase), the main metabolizing enzyme of tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy smoking in adolescence is associated with a higher risk of panic disorder, generalized anxiety disorder and agoraphobia [103]. Patients who were smokers had reduced baseline concentrations of cortisol and had higher cortisol responses to ipsapirone than nonsmokers [104], suggesting differential responses among subgroups of smoking patients with panic disorder. Unfortunately, there is a paucity of tobacco addiction treatment studies for smokers with anxiety disorders.…”
Section: Anxiety Disordersmentioning
confidence: 99%